Mulberry (Morus alba) Twig and Leaf Extracts Ameliorate Obesity-Related Metabolic Disorders via Gut Microbiota Modulation in High-Fat Diet-Fed Mice - Wei Qian; Jinyan Han; Xiang Shi; Xiaoqing Qin; Feng Jiao; Minjuan Zhang; Lijun Bao; Chao Su (Animals, 2025)
Mulberry (Morus alba) twigs and leaves, rich in flavonoids, polyphenols, polysaccharides, and alkaloids with multi-target regulatory properties on glucose/lipid metabolism, were evaluated for their anti-obesity effects using methanol-extracted twigs (MTE) and aqueous-extracted leaves (MLE) in high-fat diet (HFD)-induced obese mice. Both extracts significantly ameliorated obesity-related metabolic dysregulation, as evidenced by attenuated body weight gain, visceral fat accumulation, serum lipid profiles, homeostatic model assessment of insulin resistance (HOMA-IR), and hepatic inflammation compared to HFD controls (p < 0.05). Concurrently, MTE and MLE enhanced systemic antioxidant capacity and elevated high-density lipoprotein cholesterol (HDL-C) levels. Notably, high-dose MTE (MTEH, 1000 mg/kg) markedly reduced perirenal adiposity while increasing brown adipose tissue mass (p < 0.05). Mechanistic investigations revealed that MTEH reshaped gut microbiota composition by suppressing Firmicutes and Enterococcus, while enriching beneficial Faecalibaculum and Bifidobacterium spp. (p < 0.05). Furthermore, cecal short-chain fatty acid (SCFA) profiling demonstrated MTEH and MLEH-mediated metabolic reprogramming, characterized by increased propionic acid and decreased butyric acid, suggesting microbiota-dependent modulation of host energy metabolism. These findings collectively highlight the potential of mulberry extracts as multi-targeted nutraceuticals for obesity intervention via gut microbiota–SCFA axis regulation.